Highly stable heterostructured Ag–AgBr/TiO2 composite : a bifunctional visible-light active photocatalyst for destruction of ibuprofen and bacteria - Wang, Xiaoping (2013)
A bifunctional visible-light photocatalyst Ag–AgBr/TiO2 was synthesized by a facile one-pot method. The three-component composite exhibited much superior visible-light photocatalytic activities for ibuprofen (IBP) degradation and mineralization as compared to single-component (TiO2) and two-component (Ag/TiO2, Ag–AgBr) systems, as well as the conventional Ag–AgBr/P25. After 6 h of white LED irradiation, 81% of organic carbon could be mineralized along with decreased aromaticity and toxicity of the IBP degradation products. Meanwhile, the synthesized Ag–AgBr/TiO2 exhibited much stronger antibacterial activities than TiO2 and conventional Ag–AgBr/P25 under white LED irradiation. More interestingly, the Ag–AgBr/TiO2 had novel antibacterial activities against E. coli in the dark as compared to other Ag–AgBr/semiconductor photocatalysts that have been reported. For the first time, the action spectrum of Ag–AgBr/TiO2 was investigated using different colors of LED to elucidate the roles of Ag nanoparticles and AgBr in its visible-light photocatalytic activity. It reveals that both AgBr and Ag nanoparticles were photoactive species contributing to the high photocatalytic performance. Among the various oxidative species (h+, ˙OH, O2˙− and 1O2), O2˙− was the predominant species involved in IBP degradation upon the Ag–AgBr/TiO2 under white LED irradiation. The visible-light photocatalytic mechanism of Ag–AgBr/TiO2 and factor contributing to its high photostability in water are proposed.